Amadori-glycated phosphatidylethanolamine enhances the physical stability and selective targeting ability of liposomes. Issue 2 (14th February 2018) - Miyazawa, Taiki; Kamiyoshihara, Reina; Shimizu, Naoki; Harigae, Takahiro; Otoki, Yurika; Ito, Junya; Kato, Shunji; Miyazawa, Teruo; Nakagawa, Kiyotaka
Abstract : Liposomes consisting of 100% phosphatidylcholine exhibit poor membrane fusion, cellular uptake and selective targeting capacities. To overcome these limitations, we used Amadori-glycated phosphatidylethanolamine, which is universally present in animals and commonly consumed in foods. We found that liposomes containing Amadori-glycated phosphatidylethanolamine exhibited significantly reduced negative membrane potential and demonstrated high cellular uptake.